Os sons de uma nação imaginada: as identidades musicais de Heitor Villa-Lobos - Loque Arcanjo Junior (2013)
This thesis is objeito resizing the central historiographical study of musical identities of Heitor Villa-Lobos (1887-1959). For this, the thesis focuses on the analysis of new studies on modernism in Brazil that are currently looking for a more complex understanding of the meanings of "modern" in Brazil. These studies looked at building a centrality, by the actors São Paulo and also by the history surrounding the events of Modern Art Week 1922 and the "myth of paulistanidade" as a framework for building a national consciousness. To relativize this centrality, this same historiography resized modernism in Brazil who presented much more complex. This complexity has made historians realize other ways to build the concept of "modern", from the perception of historical dynamics built in other places and times. While recognizing the commonalities with São Paulo modernism, modernism carioca this historiography emerged as a particular historic building in the exercise of imagining the Brazilian nation. As part of the downsizing of the studies on the relationship between modernism and the relations with the different ways of imagining the nation, the current historiography resized spaces and, in trying to think about the different identities modernist became interested increasingly by revaluation the study of the relationship of modernism in Brazil with Europe) especially with France and Germany), with Hispanic America and the United States. It is in this perspective that the musical identities of Heitor Villa-Lobos are here worked. Amid the design of their social networks throughout his artistic career, the composer has established alliances, approaches, friendships, but also distancing, hostility, hatred and detractors. The construction of these networks will here perceive by the presence / absence of musical languages in which case history of the representations can be viewed not only from the aesthetic point of view or technician. The musical language, represented by scores and sound recordings, presents a set of loaded signficados assigned to it by the actors that make up the various networks built by Villa-Lobos. Although a typology of privileged source for the study of the composition of these identity networks other sources, such as letters, journals, magazines, concert programs, works musicaológicas are fundamental. Thus, the character, Heitor Villa-Lobos, emerged from sources drawing and being drawn as the modernist Carioca Belle Époque-wheels Choro Carioca, the modernist "pioneer" Week of Modern Art, and conciliatory Bachian the years 1930 and 1940. Inside the historiographical perspective that indicates the need for resizing the study of modernism in Brazil's relations with Villa-Lobos projects musicological and musical languages brought to Brazil by two Germans, Franz and Kurt J. Lange Koellreuter made explicit a detachment that was configured based on the historical context of the 1930s and 1940s, involving the Second World War, the Cold War and the emergence of the U.S. as hegemonic power. In this sense, the distance of Villa-Lobos in relation to the projects of the two German musicians and rapprochement with the United States make up the picture of himself and his work painted by Villa-Lobos along its trajectory of choices that resulted in approximations own meanings and differences with the fundamental exercise of imagining a nation Brazilian music.